Endometrial ablation plus levonorgestrel releasing intrauterine system versus endometrial ablation alone in women with heavy menstrual bleeding: study protocol of a multicentre randomised controlled trial; MIRA2 trial - Tamara J. Oderkerk; Pleun Beelen; Peggy M. A. J. Geomini; Malou C. Herman; Jaklien C. Leemans; Ruben G. Duijnhoven; Judith E. Bosmans; Justine N. Pannekoek; Thomas J. Clark; Ben Willem J. Mol; Marlies Y. Bongers (BMC, 2022)
Abstract Background It is estimated that between 12 to 25% of women who undergo an endometrial ablation for heavy menstrual bleeding (HMB) are dissatisfied after two years because of recurrent menstrual bleeding and/or cyclical pelvic pain, with around 15% of these women ultimately having a hysterectomy. The insertion of a levonorgestrel-releasing intrauterine system (LNG-IUS) immediately after endometrial ablation may inactivate residual untreated endometrium and/or inhibit the regeneration of endometrial tissue. Furthermore, the LNG-IUS may prevent agglutination of the uterine walls preventing intrauterine adhesion formation associated with endometrial ablation. In these ways, insertion of an LNG-IUS immediately after endometrial ablation might prevent subsequent hysterectomies because of persisting uterine bleeding and cyclical pelvic pain or pain that arises de novo. Hence, we evaluate if the combination of endometrial ablation and an LNG-IUS is superior to endometrial ablation alone in terms of reducing subsequent rates of hysterectomy at two years following the initial ablative procedure. Methods/design We perform a multicentre randomised controlled trial in 35 hospitals in the Netherlands. Women with heavy menstrual bleeding, who opt for treatment with endometrial ablation and without contraindication for an LNG-IUS are eligible. After informed consent, participants are randomly allocated to either endometrial ablation plus LNG-IUS or endometrial ablation alone. The primary outcome is the hysterectomy rate at 24 months following endometrial ablation. Secondary outcomes include women's satisfaction, reinterventions, complications, side effects, menstrual bleeding patterns, quality of life, societal costs. Discussion The results of this study will help clinicians inform women with HMB who opt for treatment with endometrial ablation about whether concomitant use of the LNG-IUS is beneficial for reducing the need for hysterectomy due to ongoing bleeding and/or pain symptoms. Trial registration Dutch Trial registration: NL7817. Registered 20 June 2019, https://www.trialregister.nl/trial/7817 .